2020
DOI: 10.3390/ani10122205
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Histopathological Alterations in Different Tissues of Rats Due to Repeated Oral Dose Toxicity of Cymoxanil

Abstract: Evaluating potential adverse health impacts caused by pesticides is an important parameter in human toxicity. This study focuses on the importance of subchronic toxicity assessment of cymoxanil fungicide in rats with special reference to target biochemical enzymes and histopathological changes in different tissues. In this regard, a 21-day toxicity study with repeated cymoxanil oral doses was conducted. It has been shown that low doses (0.5 mg/kg) were less effective than medium (1 mg/kg) and high (2 mg/kg) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
(56 reference statements)
2
10
0
Order By: Relevance
“…The objective of this study was to determine the protective role of ginger (100 mg/kg BW) according to Fayrouz et al [26] on hormones of male New Zealand White rabbits, dimethoate was given as measurements of sublethal (43.2 mg/kg BW each other day for 12 weeks) [27]. The LD50 of DM when given orally to rabbits was reported to be 10 000 mg/kg BW respectively [28]. Rabbits were orally administered their respective doses for 3 month.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of this study was to determine the protective role of ginger (100 mg/kg BW) according to Fayrouz et al [26] on hormones of male New Zealand White rabbits, dimethoate was given as measurements of sublethal (43.2 mg/kg BW each other day for 12 weeks) [27]. The LD50 of DM when given orally to rabbits was reported to be 10 000 mg/kg BW respectively [28]. Rabbits were orally administered their respective doses for 3 month.…”
Section: Methodsmentioning
confidence: 99%
“…The liver is the primary organ concerned with the biotransformation of chemicals, which mostly results in markedly detrimental effects on the biochemistry of hepatocytes, such as excessive ROS generation, which causes oxidative damage not only in the liver but also in other organs, including the kidneys, spleen, and hematopoietic system (36,(43)(44)(45)(46)(47)(48)(49)(50). In this study, Bz-treated rats revealed significant increases in serum bioactivities of AST, ALT, ALP, and LDH and decreased serum total protein, albumin, and α2-and γ-globulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Descotes et al, 1996 [70], reported focal basophilia of renal tubules in rats following daily intragastric treatment with cyclosporine A. Another study reported that a high dose (2 mg/kg) of cymoxanil in rats showed piecemeal necrosis in the liver combined with interstitial nephritis and tubular degeneration in the kidney [72]. In the same line, no obvious changes were recorded in the brain of rats following treatment with a low dose (0.5 mg/kg) of malathion for 21 consecutive days [69].…”
Section: Discussionmentioning
confidence: 99%